Effect of calcitonin and calcitonin gene-related peptide on pancreatic functions in man. Issue 2 (February 1988) - Beglinger, C; Koehler, E; Born, W; Fischer, J A; Keller, U; Hanssen, L E; Gyr, K
Abstract : Calcitonin gene-related peptide (CGRP) has recently been identified in central and peripheral nerve fibres, including those of blood vessels supplying the exocrine pancreas, and in pancreatic islet cells. Moreover, receptors have been characterised in the same tissue. The present study examined the effects of human CGRP and of calcitonin on exocrine pancreatic secretion and on islet cell function in nine healthy volunteers. CGRP (300 ng/kg/h) caused, respectively, a 25% and 31% inhibition of caerulein stimulated trypsin and amylase output which was similar to that seen with calcitonin (300 ng/kg/h). Arginine stimulated insulin and glucagon release was unaffected by either CGRP, or calcitonin. Calcitonin gene-related peptide caused cutaneous flushing, but did not affect the pulse rate or arterial blood pressure in the doses tested. Calcitonin gene-related peptide inhibits exocrine pancreatic secretion in vivo in man, but does not affect islet cell hormone release.